High-intense training for swimmers: features of planning and organization - Grigan S.A. ,; Raskita E.P. ,; Sorokin V.A. ,; Chebanova R.A. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the possibility of increasing the effectiveness of the training process of swimmers through the use of high-intensity training. Methods and structure of the study. The experiment, which lasted 18 weeks, involved 15 swimmers aged 17-18 years. All athletes trained according to a special program with reduced volume and high intensity. Results and conclusions. During the training process with the introduction of «high-intensity training», results were improved at all analyzed distances. In this case, the average result was determined as the arithmetic mean of the results of the swimmers of the research group.